Characterization of methanol utilization negative Pichia pastoris for secreted protein production: New cultivation strategies for current and future applications. Issue 5 (24th February 2020) - Zavec, Domen; Gasser, Brigitte; Mattanovich, Diethard
Abstract: The methanol utilization (Mut) phenotype in the yeast Pichia pastoris (syn. Komagataella spp.) is defined by the deletion of the genes AOX1 and AOX2 . The Mut − phenotype cannot grow on methanol as a single carbon source. We assessed the Mut − phenotype for secreted recombinant protein production. The methanol inducible AOX1 promoter (P AOX1 ) was active in the Mut − phenotype and showed adequate eGFP fluorescence levels and protein yields (YP/X ) in small‐scale screenings. Different bioreactor cultivation scenarios with methanol excess concentrations were tested using P AOX1 HSA and P AOX1 vHH expression constructs. Scenario B comprising a glucose‐methanol phase and a 72‐hr‐long methanol only phase was the best performing, producing 531 mg/L HSA and 1631 mg/L vHH. 61% of the HSA was produced in the methanol only phase where no biomass growth was observed, representing a special case of growth independent production. By using the Mut − phenotype, the oxygen demand, heat output, and specific methanol uptake ( q methanol ) in the methanol phase were reduced by more than 80% compared with the Mut S phenotype. The highlighted improved process parameters coupled with growth independent protein production are overlooked benefits of the Mut − strain for current and future applications in the field of recombinant protein production. Abstract : Two key genes necessary for methylotrophy in the yeast Pichia pastoris were disrupted. The strain was characterized in terms of bioprocess parameters and recombinant protein production under methanol induction. Different bioprocesses were tested and compared to the commonly used Mut S strain and bioprocess. The strain showed reduced heat evolution and oxygen demand as well as the capability of recombinant protein production without a noticeable biomass increase.